An experimental study of the efficiency of optimal control for lifting machines - Grigorov, Otto; Strizhak, Vsevolod; Strizhak, Marjana; Okun, Anton; Anishchenko, Galina (University politehnica of Bucharest, 2019)
The article is devoted to the synthesis of optimal speed performance control, in which the Pontryagin maximum principle and the phase-plane method are used to search for switching points of the relay control function. A crane trolley model and computer control system, able to implement the automatic movement of the trolley according to the optimal laws, were developed. The conducted experimental study allowed us to establish that the operating cycle of the traveling mechanism can be reduced by 1.5-3.1 times using optimal speed performance control.
Keywords: integration methods; speed performance; traveling mechanism; dynamic model; jib rotary crane